1999
DOI: 10.1097/00007632-199902150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Spondylolysis Fixation Techniques

Abstract: All four fixation techniques restored the intervertebral rotational displacements under flexion and torsional loading to the intact condition. The screw-rod-hook fixation allowed the least amount of motion across the defect during flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 25 publications
1
56
0
3
Order By: Relevance
“…2,4,8 However, data on the usage and outcomes of these different surgical techniques are limited, especially in the adolescent population with spondylolysis. 6 As athletics becomes increasing competitive and important to adolescent patients vying for college scholarships, it behooves the spine surgeon to evaluate spondylolysis fixation techniques.…”
mentioning
confidence: 99%
“…2,4,8 However, data on the usage and outcomes of these different surgical techniques are limited, especially in the adolescent population with spondylolysis. 6 As athletics becomes increasing competitive and important to adolescent patients vying for college scholarships, it behooves the spine surgeon to evaluate spondylolysis fixation techniques.…”
mentioning
confidence: 99%
“…The screw-rod-hook construct again was noted to have the greatest stiffness and the least motion across the pars defect. 10 Interestingly, this finding goes against earlier biomechanial work by Crawford and colleagues, 7 who found that greater stiffness and yield strength were achieved with Buck's technique than with the Morscher hook-screw construct and wiring technique. In the present series, we used a fully threaded lag screw, fluoroscopic guidance, and placement of rhBMP-2 across the fracture site.…”
Section: Discussionmentioning
confidence: 80%
“…Reported complications include nerve injury, screw protrusion/ backout, screw malpositioning, screw loosening, pseudarthrosis, and iliac crest graft donor-site pain. 10,57,61 Overall, complication rates have been reported to be as high as 40% with the Buck technique, 14% with Scott's wiring, and 44% with Morscher's technique. 4,5,11,27,43,44,60 The authors report no intraoperative complications in the present series.…”
Section: Complicationsmentioning
confidence: 99%
“…The constructs have to overcome the high stresses on the pars with extension and torsion. They should also not interfere with the surface area for bone grafting [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some of those have been technically difficult to perform or biomechanically inadequate to handle the forces across the pars interarticularis resulting in high failure rates [14]. In this study, we present a modified technique for direct pars repair using screws across the pedicles and sublaminar cables, together with the results of the procedure clinically and radiologically.…”
Section: Introductionmentioning
confidence: 99%